Penerapan Terapi Guided Imagery Kombinasi Aroma Terapi Lavender Terhadap Penurunan Skala Nyeri Pada Ibu Inpatru Kala I Di Ruang VK RSUD Prof. Dr. H. Aloei Saboe Kota Gorontalo - Harismayanti; Maani, Indriyati Wahyuni (Jurnal Keperawatan Muhammadiyah, 2024)
Objective:Labor pain is a natural defense mechanism for the danger signs of pregnancy and discomfort when experiencing uterine contractions. Guided Imagery non-pharmacological therapy aims to increase the patient's ability to tolerate pain. The aim of this research is to determine the application of Guided Imagery, a combination of lavender aroma therapy to reduce pain in mothers in the first stage of birth. Methods:The research method used is pre-experimental research with one group pre-post test design. The sample that will be used in this research is 17 respondents from pregnant women who experienced labor pain due to uterine contractions. Results:The results of the research showed that the majority of respondents, before the guided imagery was applied, the lavender aroma therapy combination showed a severe pain scale and after the guided imagery was applied, the lavender aroma therapy combination showed a moderate pain scale in the VK RSUD room. Prof. Dr. H. Aloei Saboe Gorontalo City. After carrying out the test using the Wilcoxon test, the P value = 0.005 with a significance level of <0.05 where P-Value=0.005 <0.05. Conclusion:Thus, it can be concluded that Ha was accepted, which means that there was an effect of implementing guided imagery therapy combined with lavender aroma therapy on first-stage mothers in the VK room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City.